BUILD CUSTOMER LOYALTY HU NEWSPAPER COMPASS - Sembiring, Ulung (Dinasti International Journal of Management Science, 2020)
Companies engaged in the industry of Newspapers in Jakarta faced the problems to maintain and increase customer loyalty. In strategic marketing, failure to maintain and increase customer loyalty greatly interfere with the performance of the company. This is reasonable because customer loyalty is an important component of corporate performance. If this happens then the company will have difficulties in maintaining and developing the internal resources and advantages. Companies that are not able to maintain and develop the internal resources and advantages are threatened with bankruptcy because it will have implications on revenue. The purpose of this study was to determine the customer relations HU Compass, Compass HU determine product attributes, relations determine the effect of customer and product attributes on customer value HU Compass, relations determine the effect of customer and product attributes on customer loyalty HU Compass. determine the effect of customer value on customer loyalty HU Compass. The method used is descriptive and survey method explanatory survey with a sample size of 70 customers HU Compass in South Jakarta as the unit of analysis.